Husband’s involvement in family planning programs: A scoping review - Lesdianti, Kiki; Hidayat, Asri (Alma Ata University Press, 2025)
Background: The use of family planning or contraception programs is still gender biased in the process of family-based national development. Husbands are often not involved in family planning programs. In fact, the involvement of husbands in the use of contraception greatly influences decision-making and the choice of contraception used. Objectives: The purpose of this study was to identify the involvement of husbands in the use of family planning programs. Methods: This scoping review uses the PRISMA-Scr and Arksey & Malley frameworks with literature searches using the Pubmed, ScienceDirect, Wiley Library, Taylor & Francis, and Sagepub databases, which were then filtered using Mendeley software and critical appraisal using the Joanna Briggs Institute (JBI). Results: The results of the search for 579 articles and selected ten articles that met the inclusion and exclusion criteria. Three main themes were obtained. The first theme was the involvement of husbands in the form of providing support/approval and participating in joint decision-making. Second, factors that influence husband involvement in the form of communication/joint discussion, access to information, sociodemographic factors (education, knowledge, work, place of residence, and number of children), and third are barriers to husband involvement in the form of sociocultural factors (gender norms and roles, religious beliefs, stigma, and side effects). From the articles, it was found that the level of husband involvement in the family planning program was relatively low. So, a strategy is needed to increase the husband's involvement. Conclusions: The available evidence discusses the husband's involvement in the use of family planning programs. Several things that are highlighted are the low level of husband involvement, factors that influence husband involvement, and barriers to the use of contraception. To increase husband involvement in the use of family planning methods with various efforts such as providing access to family planning program services and information related to family planning programs